Eating disorders and sexuality: A quantitative study in a French medically assisted procreation course. Issue 8 (17th June 2021) - Audier‐Bourgain, Marie; Baubet, Thierry; Pham‐Scottez, Alexandra; Corcos, Maurice; Nicolas, Isabelle
Abstract: Objective: Among medically assisted procreation (MAP) patients, the prevalence of eating disorders (ED), clinical or subclinical, current or past, is considerable. In addition to metabolic repercussions, the literature suggests that these patients present with more sexual dysfunction, leading to anxiety. This quantitative research on a population of women consulting a MAP department for unexplained or ovulatory infertility proposed to study the sexuality of this population by comparing the sexuality of patients suffering from or having suffered from an ED to the sexuality of the non‐ED group. Method: Patients ( n = 61) filled out the Eating Disorder Examination Questionnaire (EDE‐Q), the Brief Index of Sexual Functioning for Women (BISF‐W), the ED Whole Life Research Questionnaire, the Hospital Anxiety and Depression Scale (HADS) and the Kansas Marital Satisfaction Scale (KMSS). Results: We found a prevalence of 54% of ED, current or past. Even though these patients reported the same prevalence of sexual intercourse, they had significantly more physical problems (e.g., anorgasmia, vaginismus, headache) affecting their sexuality ( p = .01) than the non‐ED group, after adjusting for depression. Approximately 10% of the study population reported no intravaginal intercourse during the last month. Discussion: This study provides evidence for the existence of more sexual dysfunction in patients who have a fertility disorder and have ED or a history of ED. Future research should evaluate the results of psychological or sexological care that may be more suitable for the infertility of these patients. Abstract : Our article explores the sexuality of patients suffering from an eating disorders or having a history of eating disorders, and consulting with a diagnosis of ovulatory infertility or unexplained infertility in Medically Assisted Procreation (MAP) departement. The objective was to find out if the use of MAP tehniques could respond to sexual dysfunction within the couple. No difference in the number of vaginal penetrations has been found but sexuality is described as more problematic.